Employee Needs according to ERG theory and Interpersonal Relationship in Organization Affecting Organizational Conflict in Electronic Industry That affects conflicts in organizations in the electronics industry - Chaimongkol , Nartrapee; Chienwattanasook, Krisada (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The objectives of this research were to study 1) the employee’s motivation level according to the ERG theory, interpersonal relationship according to Sangahavatthu-4 and organizational conflict; and 2) influence of employee’s motivation according to ERG theory and interpersonal relationship according to Sangahavatthu-4 on the employee’s organizational conflicts in electronics industry. Studied population was employees working in electronics industry located in Bangkok and metropolitan area and there were 514 employees being selected as studied samples. The data collection used the questionnaire. Data analysis employed frequency, percentage, mean, standard deviation, and multiple regression analysis. The results of the study showed that employee needs in terms of employee’s relationship affected organizational conflicts in relation to relationship with colleagues and opposite direction process. In the meantime, interpersonal relationship according to Sangahavatthu-4 in terms of convincing speech and equitable treatment affected organizational conflicts in relation to work and opposite direction process. Additionally, interpersonal relationship according to Sangahavatthu-4 in terms of voluntary affected organizational conflicts in relation to work and relationship with colleagues in the same direction at the statistically significant level as of 0.05. Article history : Received 22 February 2019 Revised 1 April 2019 Accepted 2 April 2019 SIMILARITY INDEX = 0.00